2013
DOI: 10.1038/nature12347
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity-induced gut microbial metabolite promotes liver cancer through senescence secretome

Abstract: Obesity has become more prevalent in most developed countries over the past few decades, and is increasingly recognized as a major risk factor for several common types of cancer. As the worldwide obesity epidemic has shown no signs of abating, better understanding of the mechanisms underlying obesity-associated cancer is urgently needed. Although several events were proposed to be involved in obesity-associated cancer, the exact molecular mechanisms that integrate these events have remained largely unclear. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,656
2
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,862 publications
(1,717 citation statements)
references
References 38 publications
43
1,656
2
16
Order By: Relevance
“…75 It was also found that the baiJ gene was in high abundance, consistent with C. sordellii levels. 73 We reported the baiJKL operon in C. hylemonae and C. scindens which encodes a bile acid CoA transferase (baiK) with similar function and to the baiF gene, a homolog on the baiBCDEAFGHI operon (Fig.…”
Section: Bile Acid 7a/7b-dehydroxylation By Intestinal Bacteriamentioning
confidence: 69%
“…75 It was also found that the baiJ gene was in high abundance, consistent with C. sordellii levels. 73 We reported the baiJKL operon in C. hylemonae and C. scindens which encodes a bile acid CoA transferase (baiK) with similar function and to the baiF gene, a homolog on the baiBCDEAFGHI operon (Fig.…”
Section: Bile Acid 7a/7b-dehydroxylation By Intestinal Bacteriamentioning
confidence: 69%
“…B. wadsworthia, in particular, utilizes taurine-conjugated bile acids in sulphite reduction, and promotes colitis in genetically susceptible mice (Il10 À / À ) 44 . Bile acids have also been shown to cause DNA damage and promote hepatocellular carcinoma in mice 45,46 . Future research would help elucidate how the known risk factors like diet, obesity and smoking collectively act on the gut microbiome in the development of colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the deadliest and most common cancers worldwide [69]. In the development of HCC, nutrition and metabolic related factors like alcohol consumption, aflatoxin contamination in food [70], the gut microbiota [71], diabetes [72] and bodyweight [73] influence initiation and progression of HCC. To treat HCC is difficult, because its onset often occurs on top of an underlying liver disease such as hepatitis B or C virus infection, alcoholic liver disease, or non-alcoholic fatty liver disease.…”
Section: Liver Cancer Facts and Current Treatmentmentioning
confidence: 99%